2022
DOI: 10.1002/smi.3171
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on sleep of undergraduate students: A systematic literature review

Abstract: The 2019 coronavirus pandemic forced the shift to distance education aggravating mental and physical vulnerabilities of undergraduate students, including sleep. This review aims to describe sleep problem rates and prevalence, sleep pattern disruption, sleep duration, sleep quality, insomnia symptoms, psychological and socioeconomic factors affecting sleep of undergraduates in 22 countries. A systematic search for articles published from 2020 to 2021 using 'COVID-19,' 'Coronavirus,' 'Pandemic,' 'Sleep,' 'Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 146 publications
1
11
0
Order By: Relevance
“…While several studies demonstrated that pandemic-related lockdowns caused a substantial worsening of sleep quality [73][74][75], especially among female students, improved sleep quality was reported in another study on performing arts students [76]. Considering that pandemic-led restrictions were significant contributors to students sleep behavior, including bedtime schedules, sleep latency, and sleep duration [39], further studies are needed to investigate whether students sleep will return to normalcy or a new normal.…”
Section: Prevalence Of Poor Sleep Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…While several studies demonstrated that pandemic-related lockdowns caused a substantial worsening of sleep quality [73][74][75], especially among female students, improved sleep quality was reported in another study on performing arts students [76]. Considering that pandemic-led restrictions were significant contributors to students sleep behavior, including bedtime schedules, sleep latency, and sleep duration [39], further studies are needed to investigate whether students sleep will return to normalcy or a new normal.…”
Section: Prevalence Of Poor Sleep Qualitymentioning
confidence: 99%
“…Results of these studies suggest that poor sleep quality is particularly common among university students, with between 30% and 70% of students classified as poor sleepers. More recently, it has been proposed that pandemic-led restrictions were significant contributors to students sleep behavior, including bedtime schedules, sleep latency, and sleep duration, which caused a substantial worsening of their sleep quality [39]. Since the current literature is widely limited to US [10,30] and Chinese students [31,32,35], the findings may not reflect sleep quality rates among university students attending higher education in Europe, which has several different characteristics relating to living arrangements, tuition, enrollment, and infrastructure [40].…”
Section: Sleep Quality In University Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, different kinds of interventions aimed to solve sleep problems also have been studied further ( 13 , 14 ). Although some qualitative reviews summarized the characteristics of college students' sleep, bibliometric methods have not been used to comprehensively analyze the distribution and contribution of research in this field up to now ( 15 , 16 ). Hosseini et al and Darko et al pointed out that the qualitative review may have the potential bias of subjectivity ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, students usually have trouble falling asleep, which led to investigations regarding sleep patterns among international students [1]. It has been suggested that during the COVID-19 pandemic, sleep disorders would deepen among international students would be stronger [2,3]. The essence of sleep crosses over the affairs of every creature for the proper physiology of the body mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%